Memahami Transformasi Urban di Asia: Belajar dari Kasus Jakarta - Jo Santoso (Diponegoro University, 2013)
Urbanization is not a new phenomenon anymore, yet the ongoing worldwide urbanization now, seen from its dimension, acceleration, and complexity, is incomparable to the previous one. In many Asian countries, most people believe that creating a city as an economic growth machine is the only way to overcome the problem of urbanization development. This trend has pushed the cities away from their primary function as a human habitat which is built based on the coexistence among social groups that live there. One of the factors which likely aggravates the social situation, if the economic crisis happens, is the weakened social relation among the society due to the occurrence of global economic. In this paper discusses the three processes which serve as a catalyst to the process of city restructuring that are commodification, privatization and commercialization. The result of the development is that the city functions as a social institution is increasingly ignored and worsens the social inequality.